Viable Sweetpotato Technologies in Africa (VISTA) Tanzania project - International Potato Center (2016)
During the past year, VISTA Tanzania completed and disseminated its baseline survey. The project provided 14,100 households with clean planting material and nutrition education counselling. A total of 674 community group leaders participated in the step-down training of trainers’ course entitled “Everything You Ever Wanted to Know about Sweetpotato.”